Alexander Stuart correspondence - Stuart, Alexander. 1733-1822.
ALS written by Stuart to the customs agent at York [Yorktown], Va., regarding enforcement of embargo acts.
Virginia public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Customs administration -- Virginia -- Yorktown; Embargo, 1807-1809.; Public officials